Organoids in Lung Cancer Management - Li, Yushi; Chan, Joyce W. Y.; Lau, Rainbow W. H.; Cheung, Winnie W. Y.; Wong, Alissa Michelle; Wong, Aikha M.; Wong, Nathalie; Ng, Calvin Sze Hang (Frontiers in Surgery, 2021)
Lung cancer is a complex milieu of genomically altered cancer cells, a diverse collection of differentiated cells and non-neoplastic stroma. Lung cancer organoids is a three-dimensional structure grown from patient cancer tissue that could mimic in vivo complex behavior and cellular architecture of the cancer. Furthermore, the genomic alterations of the primary lung tumor is captured ex-vivo. Lung cancer organoids has become an important preclinical model for oncology studies in recent years. It could be used to model the development of lung cancer, investigate the process of tumorigenesis, as well as study of signaling pathways. The organoids could also be a platform to perform drug screening and biomarker validation of lung cancer, providing a promising prediction of patient-specific drug response. In this review, we described how lung cancer organoids has opened new avenues for translating basic cancer research into clinical therapy and discuss the latest and future developments in organoids technology which could be further applied in lung cancer organoids research.